2022
DOI: 10.1109/tvt.2021.3128754
|View full text |Cite
|
Sign up to set email alerts
|

Li-Ion Battery-Based Hybrid Diesel-Electric Railway Vehicle: In-Depth Life Cycle Cost Analysis

Abstract: In this study, the life cycle costs of railway projects involving hybrid diesel-electric vehicles are analysed. Specifically, the analysis focuses on the comparison of 3 lithium-ion battery technologies (NMC, LTO and LFP) and 8 energy management strategies (including rule-based and optimization-based strategies). In order to develop this analysis, a methodology that returns the life cycle cost of each proposed case is presented. The methodology includes the optimization of the diesel generator and lithium-ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…It can therefore be concluded that, in the practical test of this train system, a hydrogen fuel option would be the best way of achieving feasibility with some operating margin and without mid-trip refuelling. This finding agrees with the work of Olmos et al 14 which clearly identified a number of lines and operations in Australia, typically, longer routes without electrification options, for which the hydrogen options become essential.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It can therefore be concluded that, in the practical test of this train system, a hydrogen fuel option would be the best way of achieving feasibility with some operating margin and without mid-trip refuelling. This finding agrees with the work of Olmos et al 14 which clearly identified a number of lines and operations in Australia, typically, longer routes without electrification options, for which the hydrogen options become essential.…”
Section: Discussionsupporting
confidence: 92%
“…For typical haulage to port operations, it is usual for the gravitational potential energy to be a net train energy input. Taking all E PE energy terms as positive, we can rewrite the above equations slightly differently, ½Energy Input to the Train ¼ ½Energy Output ðConsumedÞ For Decreasing Altitude (13) For Increasing Altitude (14) For long trips, the term EKE is very small compared to other terms and so is not visible on Pie Charts. It is only non-zero if there is a difference in the speed at the end points of the section under study.…”
Section: Resultant Energymentioning
confidence: 99%
See 1 more Smart Citation
“…These models are divided into electrochemical models, electrical circuit models, and mathematical models [33]. However, the battery models proposed for sizing the storage system for railway systems are based on the mathematical models [23,34] or equivalent circuit models [35,36].…”
Section: Battery Modelmentioning
confidence: 99%
“…Research on EVs is increasing in recent years [8,9]. The main challenge in EV research is the high development cost [10][11][12]. However, EV can theoretically be applied from light to heavy vehicles.…”
Section: Introductionmentioning
confidence: 99%